Improving the Effects of Omega-3 Fatty Acid on the In Vitro Maturation of Oocytes - Masume Ghorbani Vahed; Ramazan Khanbabaee; Mehrdad Shariati; Mohammad Amin Edalatmanesh (Jurnal Ilmu Ternak dan Veteriner, 2020)
This research was conducted in order to determine the effects of omega-3 on oocyte in vitro maturation and the level of expression of tribbles (TRIB1, TRIB2 and TRIB3 genes) in cumulus cells. Eight-ten weeks old NMRI mice were super-ovulated using 7.5 IU pregnant mare’s serum gonadotropin (PMSG, Intraperitoneal) and they were killed after 44 hours and their ovaries were removed. The oocytes were used for in vitro maturation and the cumulus-oocyte complexes (COCs) were released. Cumulus cells and oocytes were assigned into control, ethanol-treated and groups exposed to 10 and 100 μg/ml of omega-3. The cells were prepared to assess the maturation stage in order to evaluate the gene expression level. The data were statistically analyzed. Exposing oocytes to low dose (10 μg/ml) and high dose (100 μg/ml) of omega-3 resulted in a reduced rate of GV-stage oocytes, decreased MI-oocytes and increased MII-oocytes. The enhanced maturity of COCs was also detected in response to a high dose of omega-3 (100 μg/ml). Exposure of cumulus cells to omega-3 (10 and 100 μg/ml) induced TRIB2 and inhibited TRIB3 gene expression level; however, TRIB1 gene expression level increased and decreased in response to low (10 μg/ml) and high (100 μg/ml) concentrations of omega-3, respectively. The addition of omega-3 to the environment of oocytes or cumulus cells affected the maturation of oocytes and cumulus cells, which was followed by the differential expression of TRIB genes, suggesting that there was a role of fatty acid metabolism in the differentiation and maturation of cumulus cells.